Peripheral ossifying fibroma - Rallan, Mandeep (BMJ Publishing Group, 2013)
Peripheral ossifying fibroma is a gingival growth, usually arising from interdental papilla and occurring frequently in the anterior maxilla. It represents upto 2% of all lesions that are biopsied. Other terms used to describe this lesion include peripheral ossifying fibroma, peripheral cementifying fibroma and calcified or ossified fibrous epulis. Paediatric patients with such a lesion have special management considerations as it requires early recognition and treatment. It requires proper treatment protocol with close postoperative follow-up. This case report presents a 12-year-old boy with an unusually large lesion in relation to the palatal aspect of the maxillary anterior teeth and its management.